URGENSI PENDIDIKAN KELUARGA DAN SEKOLAH UNTUK MENINGKATKAN KUALITAS PENDIDIKAN ANAK DALAM PERSPEKTIF HADIST - Cecep Hidayat; Zainal Arifin; Ajat Rukajat (Universitas Pakuan, 2021)
THE URGENCY OF FAMILY AND SCHOOL EDUCATION TO IMPROVE THE QUALITY OF CHILDREN'S EDUCATION IN THE PERSPECTIVE OF HADITH The family is the foundation for the mental and moral development of the child, it is the family that provides the first education before he enters the world of school and the surrounding environment. independent, educators in informal education are under the responsibility of parents, parents are the first and foremost educators for their children. The purpose of this study is to determine the extent to which family education will have an influence on the quality of education in schools at the age of 6 to 12 years and according to the review of Bukhori's sahih hadith at SDN CURUG IV Kec. Klari Kab. Karwang by using descriptive qualitative research methods based on philosophy postpositism, is used to examine natural objects, where the researcher as an instrument for data collection techniques is carried out tringulation (a combination of inductive / qualitative data analysis and qualitative research results emphasizes the meaning of generalization. That the role of parents in developing potentials that have been brought by Children from birth, it is the parents who will color and determine the child's personality in the future. The potentials that the child brings will only be able to develop properly through education provided by parents from an early age (from birth) which will then lead to the quality of the child when at school. Ah. The family is the ideal place to deliver character education, in the family the child will learn a lot practically through practicing and imitating the character of those around him, especially by imitating his parents.